2020
DOI: 10.1021/acs.jafc.0c01909
|View full text |Cite
|
Sign up to set email alerts
|

Turpentine Derived Secondary Amines for Sustainable Crop Protection: Synthesis, Activity Evaluation and QSAR Study

Abstract: In this study, we will report on the synthesis and application of efficient botanical agrochemicals from turpentine for sustainable crop protection. Two series of turpentine derived secondary amines were synthesized and identified by FT-IR, 1H NMR, 13C NMR, and HRMS. The herbicidal activities against Echinochloa crus-galli were evaluated. The potential toxicity of the synthesized compounds was tested by MTT cytotoxicity analysis. The effect of structure of the synthesized secondary amines and corresponding Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…p ‐Menth‐3‐enylamine, cis‐ 1,8‐ p ‐menthane‐diamine, and p‐ menthene‐7‐amine secondary amines were synthesized from α / β ‐pinene in our laboratory following literature procedures [16,17] . Other chemicals and reagents were commercially available and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…p ‐Menth‐3‐enylamine, cis‐ 1,8‐ p ‐menthane‐diamine, and p‐ menthene‐7‐amine secondary amines were synthesized from α / β ‐pinene in our laboratory following literature procedures [16,17] . Other chemicals and reagents were commercially available and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…The structureactivity-relationship analysis of test salts against barnyard grass further confirmed that the introduction of electron-withdrawing substituents on the benzene ring favors herbicidal activity. The relationship between the structure of the turpentine-derived secondary amines and their herbicidal activities against barnyard grass has been discussed by QSAR (Quantitative structure -activity relationship) analysis in our previous research and four values with the greatest influence on herbicidal activity were obtained, [17] which could also be applied to the new secondary ammonium chloride. Turpentine derivatives generally show low toxicity and high biocompatibility, and some of them have been widely used in the preparation of fragrances and spices.…”
Section: Herbicidal Activity Of Turpentine-derived Secondary Ammonium...mentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were grown in Dulbecco's Modified Eagle's Medium (supplemented with 10% (v/v) FBS, 100 U/mL penicillin, and 100 µg/mL streptomycin) at 37 • C in a CO 2 incubator (5% CO 2 and 95% air, 95% humidity). The effect of some compounds on cell viability was determined with the MTT assay according to the previously published literature [45,46]. A total of 5000 cells were inoculated in a 96-well plate and three wells of each concentration of test compound were used.…”
Section: Cytotoxicity Assays In Vitromentioning
confidence: 99%
“…It has been proven that secondary amines such as sec-p-menth-3-enylamines and cis-1,8-p-menthane-di-sec-amines exhibit higher herbicidal activities than that of Schiff bases, and they show low toxicity to common crops and mammal cells. 26,27 Perillaldehyde is a natural monoterpene of the p-menthane group originating from plant Perilla frutescens. It was reported that perillaldehyde displayed various bioactivities such as antidepression and antibacterial activity, 28,29 but the herbicidal activity is rarely reported.…”
Section: Introductionmentioning
confidence: 99%